Melting the secrets of gelatinisation temperature in rice - Cuevas, Rosa P.; Daygon, Venea D.; Corpuz, Henry M.; Nora, Leilani; Reinke, Russell F.; Waters, Daniel L. E.; Fitzgerald, Melissa A. (Commonwealth Scientific and Industrial Research Organisation, 2010)
Gelatinisation temperature (GT) is one of the key traits measured in programs for breeding rice (Oryza sativa L.). It is commonly estimated by the alkali spreading value (ASV), and less commonly by differential scanning calorimetry (DSC). Using a diverse set of germplasm, it was determined that DSC values associate poorly with ASV, are not correlated with amylose content but correlate with cooking time. Rice varieties are traditionally grouped into three classes of GT based on ASV: high, intermediate and low. However, the distribution of DSC values of 4000 samples shows only two classes: high and low. Large differences in the distributions of chain lengths synthesised by starch synthase IIa (SSIIa) support the two classes as the major grouping, two haplotypes associating with each peak. Each peak of DSC values spanned 10°C. The chain length distribution of the amylopectin molecules from varieties at the upper boundary of each peak showed significantly more chains that span both the crystalline and amorphous lamellae of a cluster than varieties at the other end of that distribution. Improved varieties, classified as intermediate GT by ASV, belong to both of the classes defined by DSC, implying that some enzyme, other than SSIIa is involved in intermediate GT.